Israeli labor market and the Fourth Industrial Revolution - Elisa Gotesman Bercovici; Adrian Bercovici (Amfiteatru Economic Journal, 2019)
In recent years, we have witnessed the effects of the Fourth Industrial Revolution on the labour market. Technological changes, internet use, and robotics are changing the practices, services, and needs of organizations and employees in the labour market. These changes represent both a threat and an opportunity for the significant economic development of many populations. This article aims to examine the current and expected implications of these changes in the labor market in Israel. The research presented in this article was conducted by in-depth interviews with two leading infrastructure organizations in Israel. These organizations have a broad understanding of the labour market gaps and opportunities, work with hundreds of actors in the labour market eco system (employment organizations, employees, employers, educational institutes, government, philanthropy). The results of the study suggest what some eco labour actors should do to cope with changes in the labour market due to the Fourth Industrial Revolution. We emphasis the need of new skills (up-skilling, re-skilling), Life Long Learning (LLL), new professional knowledge, and adopting further actions to older and diverse populations that will take a more significant part in the future labor market in Israel. In addition, we present some examples of programs that both researched organizations attempt to address these challenges in Israel.
Keywords: A10; D7; D8; E24; J08; 330; Industry 4.0; job mobility; employment discrimination; re-skilling; up-skilling; Life Long Learning; Non-Profit Organizations; employment organizations